Perubahan Strategis Dalam Bisnis Keluarga: Studi Kasus Sinarmas - Galieh R.D, Anastasia; Pijoh, Erick Raymond; Susetio, Agustinus Toko; Afriyanto, Arif; Aditya, Eko (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study evaluates how Sinarmas manages a structured and continuous change process. The method used is a qualitative case study with a descriptive approach, based on secondary data from annual reports, interviews with industry experts, and thematic synthesis from several accredited family business journals. Sinarmas has diversified horizontally into the real estate, telecommunications, and digital economy sectors, as well as vertical integration in the paper, agribusiness, and energy industry sectors. The shift from the founder's centralistic leadership style (one-man-show) to a hybrid leadership model with the participation of non-family professionals is a key highlight of the second- to third-generation transition strategy. The results show that family social capital such as trust and long-term vision play an important role in supporting organizational resilience. But without structural updates and innovations, this can be an obstacle to strategic adaptation. The study underscores the importance of dynamic governance and external stakeholder engagement, including in the ESG agenda, to drive sustainability. This research enriches the discourse of strategic change in Asian family businesses and proposes a conceptual model for long-term transformation in the era of disruption.